Disenchantment in the Tatras. The Vulnerability of the “Pocket Alps” (Slovakia) - Michel Lompech (Revue de Géographie Alpine)
The extraordinary storm Alžbeta (Elizabeth) of 19 November 2004 destroyed two-thirds of the forest on the slopes of the Slovakian Tatras, unveiling the extent of urbanisation and construction within the National Park. Although tourism in this mountain range started in the mid-19th century, different stages over the course of the 20th century accelerated the transformation of the mountainous surroundings into an urban and recreational area. This area is highly sensitive to natural hazards and geopolitical changes. This article presents the stages of this trajectory and the factors that make these mountains increasingly vulnerable.